ANTECEDENTS OF DIGITAL FINANCING ON MSME IN BANK SYARIAH INDONESIA (BEFORE AND AFTER MERGER) (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
The aim of this research is to analyze the antecedents (factors which influence) of digital financing at Bank Syariah Indonesia (BSI). This study is focus on data before and after merger. The population of this study is employees of BRI (Bank Rakyat Indonesia) Syariah (before merger) and BSI (after merger) This study have eight objectives to analyze the effect of antecedents (accountability, adequacy of funds, accounting information, operational risk, internal control, and credit analysis) on digital financing for MSME at BSI. The sample was determined based on the random sampling method, in which 100 respondents were obtained using the Slovin formula. All respondents were asked to fill out the questionnaire that had been prepared based on indicators of variables. Data analysis was performed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The research results indicate that from eight hypothesis, six of them are affect and two of them are not affect before merger, but after merger the results show that five of them are affect and three of them are not affect.